Nilai-nilai Kearifan Lokal pada Nilai-nilai Kearifan Lokal pada Motif Kain Tenun Gringsing di Desa Tenganan, Kecamatan Manggis, Kabupaten Karangasem : Values of Local Wisdom in the Gringsing Weaving Motif in Tenganan Village, Manggis District, Karangasem Regency - DEWI, NI PUTU NOVITA; Ni Luh Putu Tejawati; Dewa Made Alit (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mahadewa Indonesia, 2025)
This study aims to: (1) Describe the forms of motifs found in Tenun Gringsing (Gringsing woven fabric), (2) Explain the functions of the motifs in the Tenun Gringsing produced in the traditional village of Tenganan Pegringsingan, and (3) Describe the local wisdom values implemented in the daily life of the Tenganan Pegringsingan community. This research uses a descriptive qualitative approach. The subject of this research is the Tenun Gringsing fabric produced in Tenganan Pegringsingan Village, Karangasem, Bali. The data were collected through observation, in-depth interviews, and documentation techniques. The results of the study show that: (1) The process of making Tenun Gringsing includes preparing tools and materials, spinning the threads, dyeing, and binding the threads using a double ikat technique, with the final process being the finishing stage through binding. (2) The aesthetic appeal of the motifs in Tenun Gringsing emphasizes symbolic meanings, which reflect both psychological and instrumental values. (3) The main characteristics of Tenun Gringsing lie in the simplicity of its weaving, both in terms of color and motif, yet carry profound symbolic values. These characteristics are embodied in the cloth sheets, which feature a diversity of motifs inspired by natural forms. The color palette used in Tenun Gringsing is very simple, consisting only of three colors: red, black, and white. These colors represent the identity of Tenun Gringsing and the cultural identity of the people of Tenganan Pegringsingan Village, Karangasem, Bali. Keywords: Tenun Gringsing, values, local wisdom